A National Customer Satisfaction Barometer: The Swedish Experience - Fornell, Claes (Journal of Marketing, 1992)
Many individual companies and some industries monitor customer satisfaction on a continual basis, but Sweden is the first country to do so on a national level. The annual Customer Satisfaction Barometer (CSB) measures customer satisfaction in more than 30 industries and for more than 100 corporations. The new index is intended to be complementary to productivity measures. Whereas productivity basically reflects quantity of output, CSB measures quality of output (as experienced by the buyer). The author reports the results of a large-scale Swedish effort to measure quality of the total consumption process as customer satisfaction. The significance of customer satisfaction and its place within the overall strategy of the firm are discussed. An implication from examining the relationship between market share and customer satisfaction by a location model is that satisfaction should be lower in industries where supply is homogeneous and demand heterogeneous. Satisfaction should be higher when the heterogeneity/homogeneity of demand is matched by the supply. Empirical support is found for that proposition in monopolies as well as in competitive market structures. Likewise, industries in general are found to have a high level of customer satisfaction if they are highly dependent on satisfaction for repeat business. The opposite is found for industries in which companies have more captive markets. For Sweden, the 1991 results show a slight increase in CSB, which should have a positive effect on the general economic climate.